Hexanuclear Niobium Cluster Iodides with Pyridine Ligands – Temperature Induced Auto‐Oxidation. Issue 4 (10th January 2022) - Schröder, Florian; Köckerling, Martin
Abstract: The cluster compounds [Nb6 I8 Py6 ] and [Nb6 I8 Py6 ]I ⋅ 9Py, both with octahedral Nb6 metal atom cores, were obtained from the reaction of [Nb6 I11 ] with pyridine (Py). Both compounds are rare examples of iodide supported hexanuclear cluster compounds, which are obtained through solvent‐based chemical reactions. The Nb6 cluster core is surrounded by μ3 ‐bridging iodido and apical‐bonded pyridine ligands. [Nb6 I8 Py6 ] contains 22 cluster‐based electrons (CBE's), whereas [Nb6 I8 Py6 ]I ⋅ 9Py is the oxidized version with 21 CBE's. The oxidation happens just by lowering the temperature from room temperature to −20 °C of the same starting materials as used for [Nb6 I8 Py6 ]. The structures of the two cluster compounds were determined by single‐crystal X‐ray diffraction. Abstract :